Spontaneous Reattachment of a Detached Sutured Descemet-Stripping Automated Endothelial Keratoplasty Graft - Rania E. Gad; Jonathan Kahn; Danielle Trief (Case Reports in Ophthalmology, 2024)
Introduction: This is a case report of a spontaneous reattachment of Descemet-stripping automated endothelial keratoplasty (DSAEK). This graft was primarily sutured, and 20% sulfur hexafluoride (SF6) was injected into the anterior chamber, followed by graft detachment and spontaneous reattachment, 3 months later. Case Presentation: A 78-year-old male presented with DSAEK graft detachment, which was the patient’s second DSAEK (the first also did not adhere). During the second surgery, the DSAEK graft was sutured and 20% SF6 was injected intraoperatively. Graft reattachment occurred without any intervention or repositioning 3 months after the 2nd DSAEK surgery. Conclusion: Spontaneous DSEAK late graft reattachment is possible, particularly in the setting of an anchoring suture. In some patients, waiting can be an option that can spare the patient the possible risks of graft repositioning, rebubbling, or repeating the DSAEK. Suturing the DSAEK graft primarily may have served as an anchor to keep the graft approximate and aid in attachment. A graft suture can be considered in the setting of a previously failed DSAEK due to DSAEK graft detachment.